Children’s early helping in action: Piagetian developmental theory and early prosocial behavior - Hammond, Stuart I. (Frontiers in Psychology, 2014)
After a brief overview of recent research on early helping, outlining some central problems and issues, this paper examines children’s early helping through the lens of Piagetian moral and developmental theory, drawing on Piaget’s ‘Moral Judgment of the Child’ (1932/1997), ‘Play, Dreams, and Imitation in Childhood’ (1945/1951), and the ‘Grasp of Consciousness’ (1974). Piaget refers to a level of moral development in action that precedes heteronomous and autonomous moral reasoning. This action level allows children to begin to interact with people and objects. In his later work, Piaget explores the gradual construction of understanding from this activity level. Taken together, these elements of Piagetian theory provide a promising conceptual framework for understanding the development of early helping.